Taking action: Progress and challenges in implementing nutrition policies and programs - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
TO BE EFFECTIVE, COMMITMENTS TO ACTION MUST BE IMPLEMENTED AND ENFORCED. THE IMPLEMENTATION OF POLICIES AND INTERVENTIONS DEPENDS on converting political commitment to practical action. How are governments and other stakeholders doing in implementing policies and interventions that reflect commitment?